2020
DOI: 10.1515/jpm-2020-0175
|View full text |Cite
|
Sign up to set email alerts
|

The care of pregnant women during the COVID-19 pandemic – response of a large health system in metropolitan New York

Abstract: AbstractThe rapid progression of the coronavirus disease 2019 (COVID-19) outbreak presented extraordinary challenges to the US health care system, particularly straining resources in hard hit areas such as the New York metropolitan region. As a result, major changes in the delivery of obstetrical care were urgently needed, while maintaining patient safety on our maternity units. As the largest health system in the region, with 10 hospitals providing obstetrical services, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 2 publications
0
56
0
Order By: Relevance
“…Of note, early postpartum discharge was implemented at Lenox Hill Hospital on March 12th in anticipation of COVID-19 cases, followed by similar practice in the other hospitals, while an official system-wide policy for implementation was in effect on April 1st. Our guidelines suggested discharge home the day after uncomplicated vaginal deliveries and 2 days after uncomplicated cesarean deliveries using maternal criteria checklists to assure that each patient had no medical conditions or complications requiring longer stay [4]. Due to pediatric considerations and newborn testing requirements, postpartum discharge prior to 1 day was not feasible.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, early postpartum discharge was implemented at Lenox Hill Hospital on March 12th in anticipation of COVID-19 cases, followed by similar practice in the other hospitals, while an official system-wide policy for implementation was in effect on April 1st. Our guidelines suggested discharge home the day after uncomplicated vaginal deliveries and 2 days after uncomplicated cesarean deliveries using maternal criteria checklists to assure that each patient had no medical conditions or complications requiring longer stay [4]. Due to pediatric considerations and newborn testing requirements, postpartum discharge prior to 1 day was not feasible.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, hospitals within the New York metropolitan area saw a sudden influx of pregnant and nonpregnant patients with complications related to the novel coronavirus disease (COVID-19) [2]. In the face of this a public health emergency, significant changes in patient care were urgently needed in order to optimize care for obstetrical patients, accommodate the high influx of non-obstetrical COVID-19 admissions requiring increased hospital resources, as well as to decrease the potential exposure of both patients and medical staff in the hospital [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic process, telemedicine and telenursing applications have been used to meet the need for healthcare throughout the world, and skills in this area have been developed (ACOG, 2020;Nanda et al, 2020). Especially in pregnancy and postpartum follow-up and care, telehealth programs have been created, widely used (Dashraath et al, 2020;Rochelson et al, 2020). Besides, a study has shown that telehealth applications are applicable in providing prenatal care (Aziz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…After the national call for selfisolation in the UK in March 2020, staff dropped out when they were infected and also as a precautionary measure after they came in contact with a Covid-19 patients [20]. In New York, a general 14-day quarantine was imposed on all staff members who spent longer than 10 minutes within 2 meters of a Covid-19-positive patient [21]. This strict regulation was later mitigated after wearing protective masks was required [21].…”
Section: Main Topic: Structural and Organizational Challenges A Staff Shortage And Restructuringmentioning
confidence: 99%